Thermodynamic Database Update to Model Synthetic Chelating Agents in Soil Systems - Yunta, Felipe; López-Rayo, Sandra; Lucena, Juan J (Journal of Applied Solution Chemistry and Modeling, 2012)
Poliaminocarboxylate and polyaminophenolcarboxylate chelating agents, being the most representatives EDTA and o,o-EDDHA, have been profusely studied by our research team during the last 25 years because they are synthetized to be mainly used as micronutrient fertilizers to correct nutritional disorders affecting largely on crop yields placed under Mediterranean conditions. In the last years new chelating agents were designed and synthesized and the most of them were proposed to be included in the current European Directive on Fertilizers. Overall chelating agent properties, including equilibrium in soil by modeling, should be taken in account in order to check the iron chlorosis correction ability. Chemical speciation programs such as MINTEQA2, and most recently VMinteq, are being successfully used as tools to predict the behavior of each novel chelating agent in soil-plant system. Nowadays just one polyaminophenolcarboxylate chelating agent (o,o-EDDHA) is available into a VMinteq-compatible database (Lindsay's database) whereas more than seven of these type of products are authorized by European fertilizers normative to be used as micronutrient fertilizers. Therefore the aim of this work was the database updating to include all chelating agents related to o,o-EDDHA and EDTA whose complete characterization is performed and published elsewhere. Once database is updated, further modelization studies such as equilibrium reactions and adsorption isotherms with solid phase may be readily performed to get fundamental information and understand the reactivity of these recalcitrant polyaminophenolcarboxylates in soils.